PEMBERDAYAAN PEMUDA KARANG TARUNA DI DUSUN III PARIT SIPING DESA SUNGAI UNGAR UTARA KABUPATEN KARIMUN - Zainuddin; Nanik Rachmawati; Taufiqqurrachman (LPPM STISIP Persada Bunda, 2023)
In the current era it is so difficult for young people to get permanent jobs, therefore many of the youth of Dusun III still live in villages with makeshift jobs, which since a long time ago the youth have not received attention either from the community or from the chairman of the youth organization. The purpose of this research was to identify youth empowerment in Karang Taruna youth group III in Sungai Ungar Utara village. In this study the approach used is a qualitative descriptive approach and will produce descriptive data in the form of written or spoken words from people and observable behavior.This phenomenon is studied by researchers in depth using George Homans theory of social exchange. Based on the results of the study, there are three concepts, namely activities, interactions, and also feelings where activities discuss what youth youth activities are about this empowerment program, then the interactions discussed in this study are with whomever this youth organization interacts with, with the institution. what are these youth organizations interacting with. As well as the feelings discussed in this study are the feelings of Karang Taruna youth in implementing this program to be better than before, then feelings can motivate others or to themselves.